Determination of Total Flavonoid Content from Extract and Fractions of Mangrove Leaves (Rhizopora mucronata) - Sammanta, Rahula Vijja; Permatasari, Lina; Muliasari, Handa; Rachmalia Izzatul Mukhlishah, Neneng; Fersiyana Deccati, Rizqa (Acta Chimica Asiana, 2024)
Indonesia, an archipelagic country, includes Lombok Island, known for its extensive mangrove forests, where Rhizopora mucronata is the dominant species. Rhizopora mucronata, from the Rhizoporaceae family, is known for its antibacterial, antifungal, and antioxidant properties due to its secondary metabolites, including flavonoids. However, research on the flavonoid content of its leaves remains unexplored. This study aimed to determine the total flavonoid content in extracts and fractions of R. mucronata leaves using the UV-Vis spectrophotometric method. Leaves were extracted with 96% ethanol using sonication and fractionated with n-hexane, ethyl acetate, and water. The extract and fractions yielded 42.33%, 43.15%, 40.49%, 9.74%, and 32.49%, respectively. TLC tests indicated the presence of flavonoids marked by blue spots. The flavonoid contents in the extract and fractions were 12,980; 14,160; 23,880; and 25,350 mg Quercetin equivalent/gram sample (mg QE/g). The total flavonoid content was analyzed using One-way ANOVA, showing higher levels in the n-hexane and ethyl acetate fractions than in the ethanol extract and water fraction. The high flavonoid content contributes to the biological activities of R. mucronata leaves.